Partial wrap-clipping of the entrance of the pseudolumen of a fusiform aneurysm in the posterior inferior cerebellar artery: a technical note - Motoyama, Yasushi (Acta Neurochir (Wien), 2017)
BACKGROUND: Fusiform aneurysms in the posterior inferior cerebellar artery (PICA) are rare and challenging to treat. Surgical treatment options for a fusiform aneurysm in the PICA include trapping with/without bypass and wrap-clipping, when elimination of the pathological wall from the systemic circulation and prevention of perforator injury are important. In addition, lower cranial nerve impairment due to surgical manipulation should also be avoided. METHOD: A fusiform-shaped aneurysm was found in a proximal part of the PICA by magnetic resonance angiography undertaken for evaluation of repeated vertigo in a 36-year-old man. The patient underwent direct surgery via a lateral suboccipital transcondylar fossa approach. The entrance of the pseudolumen was the only part to be wrapped and obstructed by clip application, through the corridor between the acoustic and glossopharyngeal nerves to avoid lower cranial nerve injury. RESULTS: Indocyanine green (ICG) videoangiography demonstrated obliteration of pseudolumen and patency of peripheral PICA and perforator contributing to the medulla oblongata. The postoperative course was uneventful without periprocedural complications, including dysphagia and hoarseness. CONCLUSIONS: Partial wrap-clipping technique for obstruction of the entrance into a pseudolumen is one of alternatives for dissecting fusiform-shaped aneurysm in the PICA. ICG videoangiography was helpful to confirm the obliteration of the pseudolumen and patency of parent vessel and perforators.